TINGKAT DAYA TAHAN OTOT TUNGKAI ANGGOTA ORGANISASI PENCINTA ALAM SFC - Muh. Syahrul; Etno Setyagraha; Saharullah Saharullah (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
This study aims to determine how the level of members of the SFC organization. This research is a quantitative descriptive study using a survey test method, the instrument used is Half Squat Jump to measure leg muscle endurance. The sample used in this study amounted to 12 people. The data analysis technique used in this research is descriptive and percentage. The results of the descriptive test study obtained a minimum value of 24, a maximum value of 64, a total value of 536, a range of 30 and an average of 44.67 with a percentage of 0% advanced category, 0% advanced intermediate category, 91.67% intermediate category, advanced beginner category 8.33% and 0% beginner category. It can be concluded that the leg muscle endurance of members of the SFC Organization is intermediate